Soft Skills, Competition, and Hiring Discrimination - Christian Valencia; Sarah Janzen; Yashodhan Ghorpade; Amanina Abdur Rahman (Institute of Labor Economics (IZA), 2024)
We conduct a correspondence study to assess demand for soft skills in the context of hiring discrimination in Malaysia. We find no evidence of gender-based discrimination, including in STEM occupations. However, in line with previous studies in the same context, we find evidence of ethnic discrimination. We then test the relevance of two soft skills: leadership and teamwork. We find some evidence that the labor market rewards simple signals of teamwork for the average applicant. Teamwork also plays an important role in the context of labor market discrimination, reducing the discrimination gap by 40%. In contrast, signaling leadership skills has no effect. Last, we consider the role of labor market competition. Companies facing competition in the labor market, measured by the number of competitors advertising similar positions, are 56 to 66% less likely to discriminate. On the supply-side, discrimination increases with the relative quality of the pool of applicants. Our results provide novel evidence that soft skills and labor market competition both play an important role in understanding hiring discrimination. This underlines potential pathways to overcome labor market discrimination and improve job matching.
Keywords: J01; J15; J16; J24; 330; discrimination; labor market; soft skills; competition